PENGUKURAN AKUNTANSI SUMBER DAYA MANUSIA DALAM LAPORAN KEUANGAN SERTA DAMPAKNYA TERHADAP ROI PERUSAHAAN - Ibarahim H Ahmad (AkMen JURNAL ILMIAH, 2012)
This study aims to determine the relevance of the application of human resource accounting (historical human resource cost) to measure human resource as an asset of the company. The method used is descriptive comparative between conventional accounting methods with historical methods of human resource cost. The results showed that there was an increase in profits and significant cost reductions if the company uses historical methods of human resource cost than using conventional accounting methods. Similarly, the performance appraisal management companies by return on investment, ROI, the better.